Pontos de convergência entre ciência bíblica e leitura popular da Bíblia - Huning, Ralf (Revista eclesiástica brasileira, 2008)
The theme of the 12th General Assembly of the Bishops’Synod in october 2008 will be “God’s word in the life and mission of the Church”. Considering the Catholic Church’s interpretation of the Bible, the Author feels that one of the Church’s most important challenges is to overcome the gap that exists between biblical science and popular reading. Having this in mind the team working on the project “Intercultural Exegesis” developed an exegetic method –pragmalinguistics – that provides important principles for an exchange between biblical scientists and the “ordinary” readers of the Bible. The three steps used in this method – syntactic, semantic and pragmatic – may be also used as the basis for a non-scientific reading of the Bible. This should encourage a dialogue that will lead to mutual learning. While the scientific reading suggests a slow process in which the structure and the contents of the text (syntactic and semantic) are analysed in detail, popular reading offers an approximation to the action models (pragmatic) proposed by the biblical text.